Roman influences in the architecture of domes in Naples at the turn of the XVIth century - Di Liello, Salvatore (Eikonocity. Storia e Iconografia delle Città e dei Siti Europei, 2018)
In the modern age, the domes acquire a growing weight in the construction of the visual hierarchies of the urban landscape of Naples. The article focuses on the Roman influences of the Neapolitan domes at the turn of the sixteenth century when many projects - such as those of the churches of the SS. Severino and Sossio, of Santa Maria di Regina Coeli, of Santa Maria di Donnaromita and San Gregorio Armeno - among the first realizations marked by the Tridentine upgrades - seem to be part of that pauperist language affirmed in Rome by Francesco da Volterra and Martino Longhi il Vecchio. In età moderna le cupole acquistano un crescente peso nella costruzione delle gerarchie visive del paesaggio urbano di Napoli. L’articolo è incentrato sulle ascendenze romane delle cupole napoletane sul volgere del Cinquecento quando molte realizzazioni - come quelle delle chiese dei SS. Severino e Sossio, di Santa Maria di Regina Coeli, di Santa Maria di Donnaromita e San Gregorio Armeno - tra le prime realizzazioni improntate agli adeguamenti tridentini - sembrano iscriversi a quel linguaggio pauperista affermato a Roma da Francesco da Volterra e Martino Longhi il Vecchio.